Relaxation to Reduce Stress in Family Caregiver People with Mental Disorders (ODGJ)/ Relaksasi untuk Menurunkan Stres pada Family Caregiver Orang dengan Gangguan Jiwa (ODGJ) - Sandani, Aldila Putri; Rohmah, Faridah Ainur (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
People with mental disorders (PwMD) are individuals who experience disturbances in the process of thinking, behavior, and feelings that are manifested by meaningful behavioral changes and cause disruption of daily activities that make these individuals feel helpless. PwMD has a family caregiver who takes care of them every day. The family caregiver has its own burden when treating PwMD, such as having to accept the stigma from the community, economic burdens, as well as time divided for personal matters, and fears of a recurrence of the symptoms of mental disorders at any time. This burden causes stress on family caregiver. Stress is the interaction of individuals with the environment that eventually raises the gap of received demands and it causes physical and psychological reactions in family caregiver. This study aims to determine the effectiveness of relaxation to reduce stress in PwMD family caregiver. The scales that are used to measure stress levels in family caregivers are Depression, Anxiety, Stress Scale 42 (DASS 42). The research method is experimental research with one group pre-post-posttest research design with a purposive sampling technique involving 5 participants aged 34-62 years. The result of this study shows that relaxation was effective for reducing stress in PwMD family caregiver.Â Copyright Â© 2020.Â Psikoislamika: Jurnal Psikologi dan Psikologi Islam